2019
DOI: 10.1007/s10014-019-00336-z
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic and molecular aspects of anaplasia in circumscribed gliomas and glioneuronal tumors

Abstract: Many breakthroughs have been made in the past decade regarding our knowledge of the biological basis of the diffuse gliomas, the most common primary central nervous system (CNS) tumors. These tumors as a group are aggressive, associated with high mortality and have a predilection for adults. However, a subset of CNS glial and glioneuronal tumors are characterized by a more circumscribed pattern of growth and occur more commonly in children and young adults. They tend to be indolent, but our understanding of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…The use of CD34 for the prognosis, diagnosis, and treatment of various cancers has been increasing. The precise identification of CD34 noninvasively could help predicting angiogenesis-related gliomas progression [5][6][7][8]. Beside grading, CD34 expression might of assistance to indicate glioblastoma stem-like cells differentiation into tumor-associated endothelial cells in low-grade gliomas [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of CD34 for the prognosis, diagnosis, and treatment of various cancers has been increasing. The precise identification of CD34 noninvasively could help predicting angiogenesis-related gliomas progression [5][6][7][8]. Beside grading, CD34 expression might of assistance to indicate glioblastoma stem-like cells differentiation into tumor-associated endothelial cells in low-grade gliomas [62].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate grading of glioma is meaningful for clinics, however, significantly different prognosis exists among individuals who were classified as the same grade [1][2][3]. It has been fully studied that gliomas with the same or similar histological characteristics may carried different molecular or genetic information [4][5][6][7][8]. The WHO 2016 classification of CNS tumors also introduces both of the phenotype and the genotype into daily diagnosis and makes it possible to lead a more precise diagnosis of the various entities toward a personalized management of brain tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Another significant (P-value < 0.05) MeSH term, Anaplasia (D000708), is classified into the disease domain (Table 7). Anaplasia is related to neoplastic cells and refers to the loss of mature or specialized features of differentiated neoplastic cells (Rodriguez et al 2010;Pujadas et al 2019). Previous studies have shown that genetic variation among inbred mice as a result of continuous uploading and removal of rare variation (new mutations) may generate TRD (Casellas & Medrano 2008;Niu & Liang 2009).…”
Section: Functional Analysis and Gene Set Enrichmentmentioning
confidence: 99%
“…In GC-GBM, TP53 mutations are often observed, whereas mutations of IDH and TERT promoter (TERTp) are uncommon [2,3]. Lack of BRAF V600E mutation is a discriminating feature of GC-GBM from pleomorphic xanthoastrocytoma [4][5][6]. Although GC-GBM shows better prognosis compared with other classic GBM subtypes [7], the molecular biology of GC-GBM has not yet been sufficiently elucidated.…”
Section: Introductionmentioning
confidence: 99%